Type I Chaperonins: Mechanism and Beyond - Adina Breiman (Frontiers Research Topics, 2018)
Type I chaperonins are key players in maintaining the proteome of bacteria and organelles of bacterial origin. They are well known for their crucial role in mediating protein folding. For almost three decades, the molecular mechanism of chaperonin function has been the subject of intensive research. Still, surprising new mechanistic discoveries are constantly reported. It seems that we are far from having a full understanding of the chaperonin mode of action. Chaperonins are not simply protein folding machines. They also perform diverse extramitochondrial tasks, mainly related to inflammatory and signal transduction processes. This eBook constitutes ten articles highlighting the latest developments related to the divers functions of Type I chaperonins. As its title, mechanism and beyond, the collection starts with mechanistic view, continues with extracellular functions and ends with biotechnological applications of Type I chaperonins.